2020
DOI: 10.3390/coatings10101001
|View full text |Cite
|
Sign up to set email alerts
|

Recent Development of Corrosion Factors and Coating Applications in Biomass Firing Plants

Abstract: Due to global warming, biomass fuels are gradually being used to replace fossil fuels. However, high-temperature biomass corrosion is a crucial issue affecting its future application. In this article, different factors affecting boiler performance are summarized from various studies to guide the optimization of boiler parameters in practical applications, such as corrosive components and boiler temperatures. Meanwhile, different coating formation methods and materials are summarized to provide better protectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…SCC usually leads to material fatigue and cracking. This was also proved in the work of Corleto & Argade [46], who investigated a failed heat exchanger and pointed out Maribo tube [33].…”
Section: Nature Of Degradation and Its Mechanism In Heat Exchangersmentioning
confidence: 68%
See 3 more Smart Citations
“…SCC usually leads to material fatigue and cracking. This was also proved in the work of Corleto & Argade [46], who investigated a failed heat exchanger and pointed out Maribo tube [33].…”
Section: Nature Of Degradation and Its Mechanism In Heat Exchangersmentioning
confidence: 68%
“…Sadeghi et al [10] revealed that corrosion in heat exchanger components is triggered by the interaction of alloys and their oxides with chlorides, sulfates, and sulfites. Wu et al [33] also affirmed that chlorine-induced corrosion is one of the most reported cases of failure induced by chloride gas reactions with metals (active oxidation), or reaction that leads to the formation of ions (electrochemical), and the reaction occurring between chlorides (molten-salt based). Simply put, the presence of Cl-containing compounds like salt deposits formed by gaseous reactions, react with heat exchanger alloys to form alkali chlorides that penetrate through microstructural defects such as pores and cracks.…”
Section: Heat Exchangersmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the surface area can be accurately gained from the Brunauer–Emmett–Teller (BET) measurement. Apart from this method, the ECSA mainly can be obtained from three experimental techniques: 1) CO stripping voltammetry, [ 72 ] 2) underpotential deposition (upd) hydrogen (H upd ) adsorption voltammetry, [ 73 ] and 3) Cu upd stripping voltammetry. [ 74 ] In conclusion, the above six parameters discussed are important to evaluate the characteristics of electrocatalysts.…”
Section: Electrocatalytic Kinetic Measurement Criteria For Oer Hermentioning
confidence: 99%